Aspectos clínicos, epidemiológicos e histopatológicos de pacientes com carcinoma hepatocelular submetidos a transplante hepático - Tunissiolli, Nathalia Martines (2017)
Hepatocellular Carcinoma (HCC) is the primary liver cancer with high incidence and mortality rates due to its late diagnosis. Its development results from the interaction between environmental and genetic factors. Thus, the objective of this study was to evaluate clinical, epidemiological and histopathological parameters of CHC patients submitted to liver transplant surgery from 2010 to 2016 at a University Reference Center. Materials and methods: It is a retrospective, descriptive and cross-sectional study. We evaluated all HCC patients submitted to liver transplantation from 2010 to 2016 from a University Reference Center in the Northwest of São Paulo. The variables analyzed were: age, gender, ethnicity, smoking, hepatitis B virus (HBV) infection, hepatitis C virus (HCV), cirrhosis, alcoholic liver disease (ALD), diabetes, non-alcoholic fatty liver disease (NAFLD), genetic disease, alpha-fetoprotein (AFP), survival and relapse rate. Results: Of the 60 patients included in this study, 48 (80%) were men with a mean age of 58.3± 10.6 years. Cirrhosis was present in 100% of cases. The etiologies identified for the development of hepatopathy were 56.6% HCV, 20% of which were associated with alcohol, 20% of HBV, 1.66% of patients with hemochromatosis, 50.9% of ALD and 25% of NAFLD. In addition, AFP levels were measured in 42 patients, with 88.09% presenting levels below 20 ng/mL and 7.14% having levels >150 ng/mL. Regarding the histological classification of Edmondson-Steiner, 58.5% of the patients were classified as grade ≤ II and 41.5% grade ≥ III. Conclusion: Predominant male patients, with a mean age of 58.3 years. In relation to the histological classification of Edmondson-Steiner the degree ≤ II is the most frequent. Cirrhosis was prevalent in the studied patients. HCV, ALD and NAFLD were the most common etiological agents found in the study. The high prevalence of NAFLD in the pre-transplanted underestimated sample is due to the fact that all patients present cirrhosis, masking the NAFLD signals.